2016
DOI: 10.3390/ma9050390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hybridizing Flax and Hemp-Agave Fibers with Glass Fiber as Reinforcement in a Polyurethane Composite

Abstract: In this study, six combinations of flax, hemp, and glass fiber were investigated for a hybrid reinforcement system in a polyurethane (PU) composite. The natural fibers were combined with glass fibers in a PU composite in order to achieve a better mechanical reinforcement in the composite material. The effect of fiber hybridization in PU composites was evaluated through physical and mechanical properties such as water absorption (WA), specific gravity (SG), coefficient of linear thermal expansion (CLTE), flexur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…There are many studies toward hybridizations which are numerous to mention. But few amongst them include oil palm and glass fibre-reinforced epoxy composite [13], jute-glass-and kenaf-glass-reinforced polyester [14], sisaland glass-reinforced epoxy [15], and flax/glass-reinforced polyurethane polyester [16]. In all the research highlighted, the researchers manipulate the constituents of these composites and allow materials with balanced static and dynamic strength to be synthesized and used in structural or semistructural applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies toward hybridizations which are numerous to mention. But few amongst them include oil palm and glass fibre-reinforced epoxy composite [13], jute-glass-and kenaf-glass-reinforced polyester [14], sisaland glass-reinforced epoxy [15], and flax/glass-reinforced polyurethane polyester [16]. In all the research highlighted, the researchers manipulate the constituents of these composites and allow materials with balanced static and dynamic strength to be synthesized and used in structural or semistructural applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors analyzed that as the GF content increased, the pores present in the RPUF decreased, thus increasing its specific mass and, consequently, the mechanical strength. A reference value of a virgin fiber glass/PU composite can be taken in work of Pandey et al, 30 that found values of specific flexural strength between 10 MPa/ (g.cm 3 ) and 63 MPa/(g.cm 3 ), and in this research was obtained a value of 29.25 MPa/(g.cm 3 ). The difference in work of Pandey lies in the direct consolidation of the PU resin within the fibers, which may improve the surface contact between fiber and resin.…”
Section: Flexural Propertiesmentioning
confidence: 68%
“…However, these methods are not suitable for engineering applications due to their high cost and complex processes. The strength of PU can be improved by adding inorganic rigid fillers such as glass fiber and montmorillonite, but the light transmittance and toughness will be sacrificed. Therefore, the hydrogen bonding degree, crystallinity, and microphase separation degree play important roles in the adjustment of PU properties.…”
Section: Introductionmentioning
confidence: 99%